Heterogeneidade e Transferência Intergovernamental: Estudo da Zona da Mata – MG - Jéssica Natália da Silva (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2020)
The present study aims to describe the heterogeneity in the Zona da Mata Mineira and to verify if the collection of the Municipalities Participation Fund (MPF) can interfere in the quality of life of the region. For this, a factorial analysis was realized, grouping the variables of the study into three factors and constructing the Index of Quality of Life (IQL). In addition, a regression analysis was made to verify MPF interference in IQL. Results show that the region is considered heterogeneous and that MPF can interfere in the quality of life of the municipalities. Nevertheless, the onlending may be considered insufficient for municipalities to assume their responsibilities and develop themselves. The study therefore contributes to the studied region, understanding that efforts must be made to make the region less heterogeneous and more egalitarian, reflecting the advances in quality of life for the municipalities and the people who live there.